The Association Between Potato Consumption and Risk of Cardiometabolic Disorder in the Framingham Offspring Cohort Study. (29th May 2020) - Yiannakou, Ioanna; Pickering, R Taylor; Yuan, Mengjie; Singer, Martha; Moore, Lynn l
Abstract: Objectives: We examined the prospective association between potato consumption and risk of cardiometabolic disorders including hypertension, high fasting plasma triglycerides, low-density lipoproteins (LDL), and type 2 diabetes mellitus (T2DM) or impaired fasting glucose (IFG) in the prospective Framingham Offspring (FOS) cohort. We also assessed the relationship between fried or non-fried potato consumption and risk of cardiometabolic disorders. Methods: We included 2549 subjects, aged 30 years old and older. Dietary data were derived from 3-day records from examination visits 3–5. Average consumption of potatoes was classified as <1, 1–<2, 2–<4, and ≥4 cups per week. Fried and non-fried potatoes were classified as <1, 1–<3, and ≥3 cups/week. Cox proportional-hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for sex, age, education, pack-years of smoking, baseline waist and hip circumferences, fruit and non-starchy vegetable intake excluding potatoes. Results: Median follow-up was approximately 17 years. Total potato intake was not associated with increased risks of T2DM, hypertension, or abnormal fasting LDL levels but intake of 4 cups or more were associated with a 17% lower risk (95% CI: 0.68–1.02) of elevated triglycerides. Similarly, non-fried potatoes were not associated with cardiometabolic risk, although moderate intakes (vs. low) were linked with a 16% lower risk (95% CI: 0.71–1.00) of elevated LDL. Higher consumption of fried potatoes was associated with 24% decreased risk (95% CI: 0.60–0.96) of elevated triglycerides but not associated with an increased risk of other cardiometabolic factors. Conclusions: In this large cohort study, there is no adverse effect of moderate or high daily potato consumption on cardiometabolic risk factors including T2DM/IFG, hypertension, and dyslipidemia. Funding Sources: Framingham Heart Study.